MENINGKATKAN PEMECAHAN MASALAH DAN KERJASAMA MATERI PERSAMAAN SEDERHANA MENGGUNAKAN MODEL SABUMI PADA SISWA KELAS V SDN TERANTANG 2 KAB. BARITO KUALA - Dina Irsalina; Noorhapizah; Akhmad Riandy Agusta; Tika Puspita Widya Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research problem is the low problem-solving ability and collaboration skills of students, caused by abstract and passive learning methods, as well as the lack of varied learning models. The study aims to address this issue using the SABUMI model. The objectives are to describe and analyze improvements in problem-solving skills, and collaboration abilities. This research employs Classroom Action Research (CAR) with 10 fifth-grade students from SDN Terantang 2, Barito Kuala Regency, using both qualitative and quantitative approaches. The results showed that problem-solving ability increased from 60% with the criteria of